UUV Simulation Modeling and its Control Method: Simulation and Experimental Studies - Ji-Hong Li; Min-Gyu Kim; Hyungjoo Kang; Mun-Jik Lee; Gun Rae Cho (Journal of Marine Science and Engineering, 2019)
This paper presents the development of an unmanned underwater vehicle (UUV) platform, especially the derivation of the vehicle’s simulation model and its control method to overcome strong sea current. The platform is designed to have a flattened ellipsoidal exterior so as to minimize the hydrodynamic damping on the horizontal plane. Four horizontal thrusters with the identical specifications are symmetrically mounted on the horizontal plane, and each of them has the same thrust dynamics in both forward and reverse directions. In addition, there are three vertical thrusters used to handle the vehicle’s roll, pitch and heave motions. Control strategy proposed in this paper to overcome strong current is that: maximizing the vectored horizontal thrust force against the sea current without or with the least of the vehicle’s rotation on the horizontal plane. For the vehicle model, due to it being symmetric in all of three axes, the vehicle dynamics can be simplified and all of hydrodynamic coefficients are calculated through both of theoretical and empirically-derived formulas. Numerical simulations and experimental studies in both of the water tank and the circulating water channel are carried out to demonstrate the vehicle’s capability of overcoming strong current.